2017
DOI: 10.1097/mlr.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

ICD Social Codes

Abstract: SDH V codes are infrequently utilized in inpatient settings for discharges other than those related to mental health and alcohol/substance use. Utilization incentives will likely need to be developed to realize the potential benefits of cataloging SDH information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…In another study, assessment of insurance claims and EHR data of older adults provided relatively similar results with only 0.03% of claims and 0.06% of EHR’s structured data providing information related to lack of social support [12,32]. Similarly, Torres et al [15] found SBDH codes being underutilized for tracking social needs using a national sample of hospital discharges (ie, <7% of discharges in any demographic or payer subgroup). Finally, Oreskovic et al [16] developed a systematic approach to identify psychosocial risk factors within any part of a patient’s EHR record and detected an average of approximately 14 SBDH-related codes/words per Medicaid enrollee.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, assessment of insurance claims and EHR data of older adults provided relatively similar results with only 0.03% of claims and 0.06% of EHR’s structured data providing information related to lack of social support [12,32]. Similarly, Torres et al [15] found SBDH codes being underutilized for tracking social needs using a national sample of hospital discharges (ie, <7% of discharges in any demographic or payer subgroup). Finally, Oreskovic et al [16] developed a systematic approach to identify psychosocial risk factors within any part of a patient’s EHR record and detected an average of approximately 14 SBDH-related codes/words per Medicaid enrollee.…”
Section: Discussionmentioning
confidence: 94%
“…SDH is a combination of lifestyle, behavioral, social, economic, and environmental factors that are powerful drivers of health and well-being [39]. Similar to geriatric syndromes, SDH are poorly captured by diagnostic codes in EHRs [40-42]. More broadly, our success with NLP techniques for geriatric syndromes suggests that other areas that actively use SDH information to bridge the gap between population and public health may similarly benefit from EHRs’ free text and NLP techniques [43-46].…”
Section: Discussionmentioning
confidence: 99%
“…However, V‐codes are rarely used in EHRs, in less than 2 percent of hospitalizations in a national review of 2013 data 16 . There are many reasons for infrequent use of these codes.…”
Section: Introductionmentioning
confidence: 99%